THE IMPORTANCE OF FAITH AS THE FOUNDATION OF MODERN ISLAMIC EDUCATION: A LITERATURE REVIEW BASED ON THE QUR’AN AND THE SUNNAH - Sutomo Sutomo; Koko Khoerudin (Jurnal Konseling Pendidikan Islam, 2026)
Islamic education in the modern era faces complex challenges due to globalization, secularization, and the rapid flow of modernity that threatens the foundation of faith among young Muslim generations. This research aims to analyze the concept of aqidah from the perspective of the Qur'an and As-Sunnah as the fundamental foundation of Islamic education, identify the urgency of aqidah as the foundation in the modern Islamic education system, and formulate a conceptual framework for implementing aqidah in the design of modern Islamic education curriculum. This research employs library research method with a descriptive qualitative approach, where data sources consist of primary sources in the form of the Qur'an and Hadith, as well as secondary sources in the form of scientific journals, books, and articles published over the last 10 years. Data analysis uses content analysis techniques through stages of data reduction, categorization, interpretation, and drawing conclusions. The research findings indicate that: (1) aqidah in the Qur'an and As-Sunnah constitutes the epistemological and philosophical foundation that shapes students' Islamic worldview through the dimensions of tawhid (Rububiyah, Uluhiyah, and Asma wa Sifat); (2) aqidah becomes urgent as an epistemological filter, spiritual fortress, and intrinsic motivator in facing the challenges of globalization and modernity; (3) the implementation of aqidah in the curriculum requires a systematic approach through five dimensions: content, methodology, environment, evaluation, and integration with contemporary needs. This research contributes to formulating a conceptual framework for developing Islamic education that is characterized, has integrity, and is relevant to contemporary needs without neglecting aqidah as its main pillar.